ANALISIS PENGENDALIAN KUALITAS PRODUK DALAM UPAYA MENGENDALIKAN TINGKAT KERUSAKAN PRODUK EKSPOR DI PT. ASIA PACIFIC FIBERS, TBK KALIWUNGU - Muhammad Faizuddin; Poniman Poniman; Jumi Jumi (Politeknik Negeri Semarang, 2015)
This study aims to determine how the implementation of quality control of products is conducted at PT. Asia Pacific Fibers, Tbk by using statistical methods, determine the type of failure dominant products and identify the factors that cause product failure which include small bobbin, over turn yarn (OTY) and broken filament. The data collection method in this research is by direct observation at PT. Asia Pacific Fibers, Tbk by using techniques such as interview, observation, and documentation. This observation took place in March 2015. Analysis of quality control is done by using statistical methods contained in the Statistical Quality Control (SQC) such as check sheets, histograms, p charts, pareto charts and causeeffect diagram. Check sheet and histograms are used to present the data in order to make it easier to understand the data for further analysis. P Chart analysis results indicate that there are five days which are still experiencing irregularities. The defect were found on 12th, 19th, 25th, 27th, and 31st of March. Based on Pareto diagram, it is seen that failure mostly caused by small bobbin with 72.3 %, then OTY 15.1% and broken filament 12.6%. From the analysis of cause-effect diagram, it is also seen that the factors causing the failure of the products derived from human factors / workers, machinery production, working methods, materials / raw materials and work environment.